The exposure of the Great Barrier Reef to ocean acidification - Mathieu Mongin (Nature Portfolio, 2016)
As the oceans become acidic, corals reefs are threatened, generating a need to understand the driving forces controlling the chemical state of the Great Barrier Reef. Here, the authors show a greater spatial variability than previously reported, created by the interaction of reef processes and ocean circulation.